Arterial stiffness increase from adolescence to young adulthood is accelerated by smoking and alcohol use. (14th October 2021) - Walford, H C J; Hughes, A H; Charakida, M; Chaturvedi, N; Deanfield, J E; Howe, L D; Lawlor, D A; Rapala, A; Relton, C L; Park, C M
Abstract: Background: Smoking tobacco and drinking alcohol are associated with increased arterial stiffness, a critical intermediate endpoint for cardiovascular disease, in adults and in teenagers. The relationship between these risky behaviours and changes in arterial stiffness from late adolescence to early adulthood is not known. Purpose: To investigate associations between smoking and drinking habits and the change in arterial stiffness between ages 17 and 24 using a large population-based cohort. Methods: Participants underwent repeated measurements of arterial stiffness (carotid-femoral pulse wave velocity (cfPWV)), anthropometrics, resting blood pressure and blood biomarkers, at ages 17 and 24 years. Participants were grouped and scored by alcohol (never, medium intensity (MI): ≤4 drinks on a typical day of drinking, high intensity (HI): >5) and smoking (never, past, MI, <10 cigarettes a day HI, ≥10) exposure at both clinics. Average scores between clinics were taken (scores 0–5) and composite alcohol (never, MI, HI) and smoking (never, past, MI, HI) groups were created. Multivariable regression analysis was performed to investigate associations between smoking/drinking habits and change in cfPWV from 17 to 24 years (ΔPWV). Associations were adjusted for age, gender, and socioeconomic status (model 1). Model 2 was additionally adjusted for body mass index, systolic blood pressure, LDL cholesterol, glucose, and C-reactive protein at age 24. Data are presented as means (95% confidence intervals). Results: 1, 655 participants (1, 013 females and 642 males) had cfPWV recorded at both ages. cfPWV increased from 17 to 24 years in both women (ΔPWV 0.56m/s (0.50, 0.62), p<0.001) and men (0.65m/s (0.56, 0.74), p<0.001). There was a 0.05m/s (0.00, 0.10) increase in ΔPWV per 1 unit increase in average alcohol score (p=0.039). Compared to never drinkers, ΔPWV increased by 0.18m/s (−0.03, 0.38) in MI (p=0.09), and 0.21m/s (−0.01, 0.41) in HI drinkers (p=0.055). There was no association between ΔPWV and average smoking score (β=0.03m/s (−0.03, 0.08), p=0.4). Compared to never smokers, HI smokers had a slightly greater ΔPWV (0.17m/s (−0.08, 0.42), p=0.18). After stratifying by sex, this difference was evident in women (0.32m/s (0.04, 0.60), p=0.028) while no association was seen in men (−0.12m/s (−0.59, 0.35), p=0.6). No differences were found between never-smokers and ex-smokers (difference = 0.04m/s (−0.08, 0.16), p=0.5). Adjustment for potential confounders (model 2) did not attenuate these associations. Figure shows estimated marginal means for ΔPWV between (a) alcohol and (b) smoking groups from model 1. Error bars represent 95% confidence intervals. Conclusion: Smoking and alcohol use in young adulthood is associated with an accelerated increase in arterial stiffness, with evidence of a graded adverse association for alcohol. Our findings also suggest that adverse effects of smoking in youth may be reversible with smoking cessation. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation